Unorganized money markets in India - Karkal, Gopal (Bombay : Lalvani Pub. House, 1967)
The work attempts to describe both past history and the present working of the indigenous Financial Agencies in the unorganized money market and with the relationships between different indigenous agencies themselves and also the future of these agencies in the banking and credit structure of the Indian economy
"This work is an improved version of the [author's] thesis approved for the Ph. D. degree of Bombay University."
Bibliographical footnotes.
osc 7/11/17
Loans
Keywords: Credit